Association of Patient Profile with Glycemic Control and Hypoglycemia with Insulin Glargine 300 U/mL in Type 2 Diabetes: A Post Hoc Patient-Level Meta-Analysis - Twigg, Stephen M.; Escalada, Javier; Stella, Peter; Merino Trigo, Ana; Lavalle González, Fernando Javier; Cariou, Bertrand; Meneghini, Luigi F. (2018)
ABSTRACT Aims: To examine the association of baseline patient characteristics with study outcomes in people with type 2 diabetes receiving insulin glargine 300 U/mL (Gla-300) versus glargine 100 U/mL (Gla-100), over a 6-month period. Methods: A post hoc patient-level metaanalysis using data from three multicenter, randomized, open-label, parallel-group, phase 3a studies of similar design, in people previously receiving either basal and prandial insulin, basal insulin ? oral antihyperglycemic drugs, or no prior insulin (EDITION 1, 2 and 3, respectively). The endpoints, glycated hemoglobin (HbA1c), hypoglycemia, body weight change, and insulin dose were investigated by subgroups: age (\65 and C 65 years), body mass index (BMI; \ 30 and C 30 kg/m2), age at onset (\40, 40–50, and [ 50 years), and diabetes duration (\ 10 and C 10 years). Results: Reduction in HbA1c was comparable between insulins, regardless of subgroup. The lower risk of C 1 nocturnal (00:00–05:59 h) conﬁrmed (B 3.9 mmol/L [B 70 mg/dL]) or severe hypoglycemic event with Gla-300 versus Gla-100 was also unaffected by participant characteristics. While heterogeneity of treatment effect between diabetes duration subgroups was seen for the risk of C 1 conﬁrmed (B 3.9 mmol/L [B 70 mg/dL]) or severe hypoglycemic event at any time (24 h), treatment effect consistently favored Gla-300; no evidence of heterogeneity was observed for the other subgroups. Annualized rates of conﬁrmed (B 3.9 mmol/L [B 70 mg/dL]) or severe hypoglycemia and body weight change were not inﬂuenced by participant characteristics; a similar pattern was observed with insulin dose. Conclusions: Comparable glycemic control was observed with Gla-300 versus Gla-100, with less hypoglycemia, regardless of age, BMI, age at onset or diabetes duration. Funding: Sanoﬁ. Plain Language Summary: Plain language summary available for this article. Keywords: Glycated Hemoglobin A; Hypoglycemia; Insulin Glargine; Type 2 Diabetes PLAIN LANGUAGE SUMMARY Treatments for patients with type 2 diabetes aim to reduce the levels of blood glucose and can include injections with insulin. However, care must be taken to prevent blood glucose levels falling too low (a state called hypoglycemia). Previous studies have shown that insulin glargine 300 units/mL (Gla-300) provides similar reductions in blood glucose levels as insulin glargine 100 units/mL (Gla-100) but is less likely to cause hypoglycemia. However, different patients may respond differently to treatments depending on their individual clinical and biological characteristics. The aim of this study was to evaluate how different proﬁles of patients with type 2 diabetes responded to Gla-300 and Gla-100 injections. Patients were grouped by different ages, weights, age at diabetes diagnosis, and number of years since diagnosis of diabetes. We found that Gla-300 and Gla-100 reduced glycated hemoglobin (HbA1c; a marker of blood glucose control over the previous 2–3 months) similarly, regardless of how patients were grouped. However, patients treated with Gla-300 were less likely to experience hypoglycemia than those treated with Gla-100, and this association was also true regardless of different patient characteristics. We therefore concluded that Gla-300 is an effective and safe treatment in patients with type 2 diabetes, regardless of their age, weight, age at diabetes diagnosis, and years since diagnosis.